At first sight [videorecording (DVD)] - Winkler, Irwin; Kilmer, Val, 1959-; Sorvino, Mira; McGillis, Kelly, 1957-; Weber, Steven, 1961 March 4-; Davison, Bruce, 1946-; Lane, Nathan, 1956-; Sacks, Oliver, 1933-2015 (MGM Home Entertainment, 1999)
A man who has been blind since shortly after birth undergoes a surgical procedure that allows him to see again, which both enriches and complicates his life.